2023
DOI: 10.3389/fnut.2023.1132228
|View full text |Cite
|
Sign up to set email alerts
|

Integrated metabolite analysis and health-relevant in vitro functionality of white, red, and orange maize (Zea mays L.) from the Peruvian Andean race Cabanita at different maturity stages

Abstract: The high maize (Zea mays L.) diversity in Peru has been recognized worldwide, but the investigation focused on its integral health-relevant and bioactive characterization is limited. Therefore, this research aimed at studying the variability of the primary and the secondary (free and dietary fiber-bound phenolic, and carotenoid compounds) metabolites of three maize types (white, red, and orange) from the Peruvian Andean race Cabanita at different maturity stages (milk-S1, dough-S2, and mature-S3) using targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Here, we briefly summarize the reported contents of bioactive antioxidative phenolic compounds in colored flours that are expected to contribute to the health benefits of the flatbreads. Ranilla et al [10] reported on the content of bioactive compounds in white, orange, and red Peruvian corn harvested at different stages of maturity. All maize types contained free hydroxybenzoic and hydroxycinnamic acids and bounds ferulic acid, ferulic acid derivatives, and p-coumaric acid.…”
Section: Colored Corn Floursmentioning
confidence: 99%
“…Here, we briefly summarize the reported contents of bioactive antioxidative phenolic compounds in colored flours that are expected to contribute to the health benefits of the flatbreads. Ranilla et al [10] reported on the content of bioactive compounds in white, orange, and red Peruvian corn harvested at different stages of maturity. All maize types contained free hydroxybenzoic and hydroxycinnamic acids and bounds ferulic acid, ferulic acid derivatives, and p-coumaric acid.…”
Section: Colored Corn Floursmentioning
confidence: 99%
“…Alternatively, these phenolic amides are found as co-pigments in colored maize and contribute significantly to anthocyanin coloration, particularly putrescines for red and spermidine for blue-colored varieties (27). HCAAs not only exhibit variations between genotypes, kernel colors, and ecological factors but also vary across different stages of plant development (11).…”
Section: Diversity Of Hcaas In Maize Tissues and Genotypesmentioning
confidence: 99%
“…In recent times, there has been renewed interest among scientists in examining the phenolic variability present in maize landraces and commercial samples with pigmented grains, particularly in countries like Peru [7], India [8], and Italy [9]. The purpose of the previous studies, in addition to evaluating the genetic diversity, was to contribute to the visibility of these valuable plant resources, potentially leading to the discovery of new uses and applications.…”
Section: Introductionmentioning
confidence: 99%